Large-Scale Identification and Characterization of Heterodera avenae Putative Effectors Suppressing or Inducing Cell Death in Nicotiana benthamiana - Chen, Changlong; Chen, Yongpan; Jian, Heng; Yang, Dan; Dai, Yiran; Pan, Lingling; Shi, Fengwei; Yang, Shanshan; Liu, Qian (Frontiers in Plant Science, 2018)
Heterodera avenae is one of the most important plant pathogens and causes vast losses in cereal crops. As a sedentary endoparasitic nematode, H. avenae secretes effectors that modify plant defenses and promote its biotrophic infection of its hosts. However, the number of effectors involved in the interaction between H. avenae and host defenses remains unclear. Here, we report the identification of putative effectors in H. avenae that regulate plant defenses on a large scale. Our results showed that 78 of the 95 putative effectors suppressed programmed cell death (PCD) triggered by BAX and that 7 of the putative effectors themselves caused cell death in Nicotiana benthamiana. Among the cell-death-inducing effectors, three were found to be dependent on their specific domains to trigger cell death and to be expressed in esophageal gland cells by in situ hybridization. Ten candidate effectors that suppressed BAX-triggered PCD also suppressed PCD triggered by the elicitor PsojNIP and at least one R-protein/cognate effector pair, suggesting that they are active in suppressing both pattern-triggered immunity (PTI) and effector-triggered immunity (ETI). Notably, with the exception of isotig16060, these putative effectors could also suppress PCD triggered by cell-death-inducing effectors from H. avenae, indicating that those effectors may cooperate to promote nematode parasitism. Collectively, our results indicate that the majority of the tested effectors of H. avenae may play important roles in suppressing cell death induced by different elicitors in N. benthamiana.